Role of Arginine decarboxylase (ADC) in Arabidopsis thaliana defence against the pathogenic bacterium Pseudomonas viridiflava - Rossi, Franco Rubén (2014)
Polyamine biosynthesis starts with putrescine production through the decarboxylation of arginine or ornithine. In Arabidopsis thaliana, putrescine is synthesised exclusively by arginine decarboxylase (ADC), which exists as two isoforms (ADC1 and 2) that are differentially regulated by abiotic stimuli, but their role in defence against pathogens has not been studied in depth. This work analysed the participation of ADC in Arabidopsis defence against Pseudomonas viridiflava. ADC activity and expression, polyamine levels and bacterial resistance were analysed in null mutants of each ADC isoform. In non-infected wild-type (WT) plants, ADC2 expression was much higher than ADC1. Analysis of adc mutants demonstrated that ADC2 contributes to a much higher extent than ADC1 to basal ADC activity and putrescine biosynthesis. In addition, adc2 mutants showed increased basal expression of salicylic acid- and jasmonic acid-dependent PR genes. Bacterial infection induced putrescine accumulation and ADC1 expression in WT plants, but pathogen-induced putrescine accumulation was blocked in adc1 mutants. Results suggest a specific participation of ADC1 in defence, although basal resistance was not decreased by dysfunction of either of the two ADC genes. In addition, and as opposed to WT plants, bacterial infection increased ADC2 expression and ADC activity in adc1 mutants, which could counterbalance the lack of ADC1. Results demonstrate a major contribution of ADC2 to total ADC activity and the specific induction of ADC1 in response to infection. A certain degree of functional redundancy between the two isoforms in relation to their contribution to basal resistance is also evident.